Pengaruh Pembacaan Al-Quran Terhadap Kecemasan pada Lansia di Pondok Pesantren Lansia An-Nur Kota Kediri - Hanisah, Novia Eka; Kumala, Risna Nur (Spiritualita, 2025)
This research aims to prove the effect of reading the Koran on reducing anxiety during aging, especially in elderly students at the An-Nur Islamic Boarding School, Kediri City. The research used pretest and posttest methods to measure anxiety levels before and after the Al-Qur'an reading intervention (sorogan). The results showed that of the ten subjects, seven subjects experienced a decrease in anxiety after following the Al-Qur'an sorogan. Meanwhile, three subjects did not experience a significant decline due to several factors, such as health problems with memory, high emotions, and slight mental disorders. These factors contribute to anxiety triggers, namely physical weakness and poor social relationships. This positive change is believed to be influenced by the process of reading the Al-Qur'an regularly. This research concludes that reading the Koran can be an effective intervention to reduce anxiety in the elderly, especially in the context of the Islamic boarding school environment.